Prevalence of Acinetobacter baumannii in Saudi Arabia: risk factors, antimicrobial resistance patterns and mechanisms of carbapenem resistance - Mutasim E. Ibrahim (BMC, 2019)
Abstract Acinetobacter baumannii is an important opportunistic pathogen due to its capabilities for developing mechanisms of resistance to a wide range of antimicrobial agents including carbapenems. This review described the risk factors, antimicrobial susceptibility and mechanisms of carbapenem resistance of A. baumannii from different geographical regions of Saudi Arabia. Several factors including complexity of intensive care unit (ICU) environments, increased numbers of patients with serious diseases, wide spread gastrointestinal colonization and extensive use of antimicrobial drugs led to a wide prevalence of A. baumannii infections in hospitals in Saudi Arabia. A. baumannii has been noted to be less susceptible to antimicrobials agents, including carbapenems, over time, resulting in the evolution of multidrug-resistant (MDR) strains. Dissemination of MDR A. baumannii is attributed to the extreme use of wide-spectrum antimicrobial drugs in hospitals, cross infection between inpatients, invasive ICU procedures, and hospitalized patients with diabetic and cancer those are under frequent invasive diagnostic and therapeutic interventions. Although an increasing prevalence of colistin and tigecycline resistance has been reported in many hospitals, combinations of these agents with carbapenems or other antibiotics remain the best therapeutic choice and reasonably safe to treat patients with MDR A. baumannii infections. The wide distribution of carbapenem resistant A. baumannii (CRAB) due to several mechanisms with diverse genetic determinants has been documented. Although OXA-23 β-lactamase and OXA-51 β-lactamase are the most common genes responsible for CRAB, other novel genes such as blaVIM, PER-1-like and GES-5 have been discovered in carbapenem resistant strains. The high rates of MDR A. baumannii in Saudi hospitals indicate that extensive investigation into the molecular basis of MDR and developing new therapies of CRAB is needed. Moreover, the development of a local antibiogram database coupled with a nationwide antimicrobial stewardship and infection prevention program might help to improve our knowledge of the resistance patterns of A. baumannii, and in developing a treatment protocol for decreasing the infection burden in Saudi Arabia.